2017
DOI: 10.1140/epjc/s10052-017-4987-2
|View full text |Cite
|
Sign up to set email alerts
|

Leptoquark mechanism of neutrino masses within the grand unification framework

Abstract: We demonstrate the viability of the one-loop neutrino mass mechanism within the framework of grand unification when the loop particles comprise scalar leptoquarks (LQs) and quarks of the matching electric charge. This mechanism can be implemented in both supersymmetric and nonsupersymmetric models and requires the presence of at least one LQ pair. The appropriate pairs for the neutrino mass generation via the up-type and down-type quark loops are S 3 -R 2 and S 1, 3 -R 2 , respectively. We consider two distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 50 publications
1
74
0
Order By: Relevance
“…We can thus identify y of eq. (2.1) with y 45 / √ 2, where y 45 is related to the difference in masses between charged fermions and down-type quarks [52]. This follows from the fact that there are actually two operators that contribute towards the charged fermion and down-type quark masses in this SU(5) model [91].…”
Section: Jhep10(2017)188mentioning
confidence: 96%
See 3 more Smart Citations
“…We can thus identify y of eq. (2.1) with y 45 / √ 2, where y 45 is related to the difference in masses between charged fermions and down-type quarks [52]. This follows from the fact that there are actually two operators that contribute towards the charged fermion and down-type quark masses in this SU(5) model [91].…”
Section: Jhep10(2017)188mentioning
confidence: 96%
“…(2.1) since we assume that S 3 and its interactions originate from the GUT construction presented in ref. [52] where the baryon number violating diquark couplings are forbidden due to the grand unified symmetry. 1 The main goal of our study is to address the puzzles observed in neutral current LFU tests in the R K ratio (and related anomalies in b → sµ + µ − ) as well as in charged-current LFU ratios R D ( * ) .…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the context of GUTs, neutrino masses may also be generated at the loop level under the presence of heavy leptoquarks [79]. We here omit this possibility.…”
Section: A Neutrino Massesmentioning
confidence: 99%